Demystifying early childhood computational thinking: An umbrella review to upgrade the field - Weipeng Yang; Jiahong Su; Hui Li (Future in Educational Research)
Abstract By transforming abstract problems into tangible solutions, computational thinking (CT) emerges as a foundational competency. This umbrella review synthesizes the current landscape of CT in early childhood, pivotal for fostering 21st‐century skills across multiple domains. A systematic search across Scopus, ACM Digital Library, and Web of Science yielded 13 review studies for analysis, addressing the integration of CT in early childhood education. Employing a narrative synthesis approach, the review illuminated key findings and highlighted future research trajectories. Findings indicate the centrality of creating sequences and events in imparting CT in early childhood, recommending more sophisticated concepts like loops and conditionals for older children. Instructional designs unearthed include scaffolding with narratives, tangible objects, and physical embodiments, balancing structured tasks and open‐ended engagement. Three categories of computational kits were discerned: physical, virtual, and hybrid kits. The Bee‐Bot and various LEGO kits were prevalent among CT learning tools, with interfaces ranging from physical buttons to hybrid systems. Efficacy was noted in tangible activities like unplugged applications and robotics in enhancing concrete understanding and competencies in coding, CT, and spatial skills. Concluding remarks discuss research gaps, future prospects, and provide actionable insights for educators and policy makers, calling for the co‐creation of an ecosystem of CT integration across early childhood curricula.